Eco-epidemiology of arenaviruses at the rodent-human interface in Mozambique - (:unkn) unknown (My University, 2022)
Emerging infectious diseases (EIDs) have been a major global concern and more than 70% of new EIDs are zoonotic diseases that mostly originated from wildlife. EIDs caused by Lassa and Lujo mammarenaviruses are responsible for fatal cases of hemorrhagic fever in the west and southern Africa, respectively. The reservoir of the Lujo virus is yet unknown while the main reservoir of the Lassa virus is Mastomys natalensis, a rodent species widely distributed in sub-Saharan Africa. Other several mammarenaviruses yet regarded as non-pathogenic for humans were detected mainly from M. natalensis in southern Africa. Thus M. natalensis is one of the most important rodent species that carry zoonotic or potential zoonotic diseases. Moreover, the lives of rodents and people are often interwoven, increasing the interaction between rodents and humans as well as the risk of the emergence of zoonotic rodent-borne diseases.This study aims to assess the circulation of mammarenaviruses and identify their drivers at the human/rodent interface in the Limpopo National Park and its buffer zone in Mozambique, to improve our knowledge of the potential risk of emerging rodent-borne zoonotic diseases. To reach our main objective we studied rodent ecology, then we detected and genotyped Mammarenavirus in M. natalensis trapped in irrigated cropland fields, rainfed cropland fields, mopane woodland forest, and villages. We also studied the drivers of the viral circulation in M. natalensis and finally we assessed human knowledge, attitudes, and practices toward rodents.Our results indicated that the small-mammal community structure in our study area included seven rodent species and one shrew. M. natalensis was present in all four habitats sampled during the study. However, the irrigated agricultural fields constitute the main habitat for this rodent species. M. natalensis started breeding during the rainy season and its highest peak was observed in the middle of the dry season in June.
Keywords: African Research